2018
DOI: 10.2147/ijn.s162355
|View full text |Cite
|
Sign up to set email alerts
|

Nanoselenium prevents eimeriosis-induced inflammation and regulates mucin gene expression in mice jejunum

Abstract: BackgroundAlthough elemental selenium has been found to be effective against Eimeria, no study has yet investigated the effects of selenium nanoparticles (SeNPs) on the Eimeria parasite. The aim of this study, therefore, was to evaluate the ameliorative effect of SeNPs compared with elemental selenium on mice jejunum infected with sporulated oocysts of Eimeria papillata.MethodsThe mice were divided into 4 groups, with the first being the non-infected, control group, and the second, third, and fourth groups bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 43 publications
5
30
1
Order By: Relevance
“…However, the Ross broilers exhibited greater adverse effects than Arbor broilers that were supplied with the same dose of traditional commercial Se. These results were inconsistent with those of Alkhudhayri et al (2018), who reported significant and improved histological outcomes from NS supplementation in the face of environmental challenges and infection. Mousa and Ali (2018) studied the influence of nano-boron on the liver of African ostrich chicks after E. coli infection and observed the ability of nano-particles to reduce the stress factors with increased resistance.…”
Section: Tablecontrasting
confidence: 73%
“…However, the Ross broilers exhibited greater adverse effects than Arbor broilers that were supplied with the same dose of traditional commercial Se. These results were inconsistent with those of Alkhudhayri et al (2018), who reported significant and improved histological outcomes from NS supplementation in the face of environmental challenges and infection. Mousa and Ali (2018) studied the influence of nano-boron on the liver of African ostrich chicks after E. coli infection and observed the ability of nano-particles to reduce the stress factors with increased resistance.…”
Section: Tablecontrasting
confidence: 73%
“…Nanotechnology is an emerging and rapidly growing field that has raised high expectations for a variety of applications in the food and food‐related industries, including agriculture, food processing, food packaging, and dietary supplements (He & Hwang, 2016). Recent studies have listed the various benefits of nanoparticles in the food field, which are antimicrobials, increased bioavailability, and antioxidants, as well as improving some of the rheological and phenotypic properties of foods such as color and consistency (Alkhudhayri, Dkhil, & Al‐Quraishy, 2018; Dkhil et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nano-Se was shown to have antimicrobial activities against Trichophyton rubrum (Yip et al ., 2014), Candida albicans (Kheradmand et al ., 2014), Pseudomonas aeruginosa, Proteus mirabilis (Shakibaie et al ., 2015), Bacillus cereus, Enterococcus faecalis, Staphylococcus aureus, Escherichia coli O157:H7, Salmonella Typhimurium, S. Enteritidis (Khiralla and El-Deeb, 2015), S. aureus (Nguyen et al ., 2017), and Toxoplasma gondii (Keyhani et al ., 2020). Interestingly, nano-Se is more effective than sodium selenite with regard to its anti-coccidial, anti-oxidant, and anti-inflammatory role against coccidiosis induced in the jejunum of mice (Alkhudhayri et al ., 2018). Nano-Se was also shown to restrict the growth of nanobacteria (Sardarabadi et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%